Auto-CCAFS-MOT: a batch calculator tool for farmers GHG emissions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Taking advantage of the CCAFS-MOT version, we decided to go further, developing a new system, which is able to calculate GHG emissions for multiple crop events. This new development was completed on python that facilitates its integration with web applications. Besides users can download soil-data from SoilGrids.